2015
DOI: 10.1038/srep17560
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical assessment of feasibility to sequence DNA through interlayer electronic tunneling transport at aligned nanopores in bilayer graphene

Abstract: Fast, cost effective, single-shot DNA sequencing could be the prelude of a new era in genetics. As DNA encodes the information for the production of proteins in all known living beings on Earth, determining the nucleobase sequences is the first and necessary step in that direction. Graphene-based nanopore devices hold great promise for next-generation DNA sequencing. In this work, we develop a novel approach for sequencing DNA using bilayer graphene to read the interlayer conductance through the layers in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…We thus note that it could be significantly enhanced by changing the gate voltage accessing regions where the defect is more metallic in nature. Finally, regarding selectivity, we note that the binding energy of NO 2 [20] is higher than that of O 2 [53]; this not only influences the residence time, but also the electronic transport [54], thus possibly leading to good selectivity as well.…”
Section: Resultsmentioning
confidence: 90%
“…We thus note that it could be significantly enhanced by changing the gate voltage accessing regions where the defect is more metallic in nature. Finally, regarding selectivity, we note that the binding energy of NO 2 [20] is higher than that of O 2 [53]; this not only influences the residence time, but also the electronic transport [54], thus possibly leading to good selectivity as well.…”
Section: Resultsmentioning
confidence: 90%
“…The interaction energy profile observed in our simulation agrees with the force profile obtained from the ssDNA sequencing by the graphene nanopore [ 44 ]. From the experimental viewpoint, the interaction energy between the nucleobase and two-dimensional layers has a correlation with the conductance which shows a means to differentiate the four nucleobase types [ 45 ]. For example, the conductance fluctuation of pyrimidines is found to be much larger than that of purines, resulting from the interaction strength between the nucleobase and the nanopore.…”
Section: Resultsmentioning
confidence: 99%
“…Hence graphene nano-gap devices have been proposed as well. [15][16][17][18][19] The authors of this work have recently proposed a nano-gap device based on an array of semi-innite graphene nano-ribbons (GNRs) where the central gap should be devoted to the detection of peptide bonds (PBs) along the peptide back-bone. 19 It was shown that using such kinds of GNR based devices (see Fig.…”
Section: Introductionmentioning
confidence: 99%